Predicting the extent of hydrophilicity on Si nano‐column surfaces - Can, M. F.; Guvendik, S.; Benli, B.; Trabzon, L.; Kizil, H.; Celik, M. S. (Wiley, 2012)
AbstractControlling the wettability of nano textured surface structures is essential for understanding of its role particularly in biomedical applications. The main objective of this study is to explore the wetting mechanism of a water drop on a nano textured Si surface. Si nano‐columns with 4‐, 3‐ and 2‐fold in‐plane symmetries were grown on p‐type (100) Si wafer by oblique angle deposition (OAD). The surface morphology was characterized by scanning electron microscopy (SEM). The contact angle technique was used to reveal the wetting characteristics of these textured surfaces. Experimental results were compared with the theoretical contact angle calculations derived from the Young, Wenzel and Cassie‐Baxter equations in order to identify the conditions for the minimum free energy of the drop. Water droplets on all plenary symmetries water droplets showed good agreement with the Cassie‐Baxter model of Sunny side up. These findings were used to simulate the extent of the hydrophilicity on the fabricated textures by taking the contact angle hysteresis (CAH) into account.
Keywords: Cassie-Baxter-Modell; Benetzbarkeit; wettability; Cassie-Baxter model; Kontaktwinkel; nano-column; hydrophilic surface; hydrophile Oberflache; Nanosaule; contact angle